Factors affecting adoption behaviour of agroforestry practitioners in ATISBO local Government Area of Oyo State, Nigeria (2007)
The importance of trees and shrubs in fallows or in food crop production systems cannot be overstressed in view of the fragile nature of the tropical environment, increase in population density, rate of forest diminution and increasing land shortage. This has given rise to the technology of Agroforestry. Evolving technology to meet any need will be incomplete without taking cognizance of the end-users no matter how perfect. This study investigates the factors affecting adoption behaviour of agroforestry practitioners in Atisbo local Government Area of Oyo State, Using a purposive random technique, a total of one hundred and fifty questionnaires were administered to selected agroforestry farmers in the study area based on membership of Alisbo Farmers' Association of Nigeria (AFAN). Data generated were analyzed using descriptive and inferential test statistics. Results reveal variants of agroforestry system among the respondents. These include; the tree crop system (67.3%); Mixed home gardening (22.7%); Alley cropping (7.3%); Bush fallow (2.0%); and Taungya (0.7%). Farmers income level and extension contact were two variables that significantly associate with adoption of agroforestry technology (X2 7.651, 47. 680; P<0.05). There is also a positive and significant correlation between adoption and scale of farming, total farm size, socio status on land and type of agroforestry system. The financial implication of practicing agroforestry system is the most important determining factor affecting adoption and application.